Diagnostic value of p53 immunohistochemical expression in high-grade serous ovarian carcinoma (HGSC): casuistry in our center in the last three years. - Ortega-Jiménez, María Victoria; Ramírez Sánchez, C.; Hierro-Martín, María Isabel (My University, 2022)
High-grade serous carcinoma (HGSC) is the most common ovarian carcinoma (70%). Age over 60 years, a family history of breast/ovarian carcinoma, and infertility are risk factors. Etiology remains unknown. These tumours arise from tubal-type epithelium, usually in the fallopian fimbria and less commonly in the ovarian surface or within ovarian epithelial inclusion cysts. Nearly every tumour harbours a deleterious TP53 mutation [1].[ Methods: A review of all cases diagnosed in our centre of high-grade serous ovarian carcinoma in surgical specimens, between 1 January 2019 and 31 December 2021, was carried out. The immunohistochemical profile (WT-1, p16 and p53) was compared with the results obtained in the massive NGS sequencing panel, focusing on the study of p53. Results: In our centre, 32 cases of high-grade ovarian serous carcinoma were diagnosed in 2019, 2020 and 2021, of which 31 showed a mutates immunohistochemical staining pattern (65% with p53 overexpression and 32% with null pattern), and 1 a non-mutated pattern. Of these 31 patients, 19 (61%) underwent genetic sequencing (Oncomine). Of these 19 patients, 16 (84%) had a p53 somatic lineage mutation and 3 (16%) were non-mutated. Immunostaining was positive for p16 in 30 cases, with intense cytoplasmic and nuclear staining expression in 27 of them and patchy and diffuse in 3, WT1 was positive in all of them. Discussion and conclusions: In this case series we would like to share our centre´s case reports on this pathology, with special emphasis on the importance of p53 immunohistochemical staining as a surrogate marker for sequencing techniques. Its use allows patients to be classified into high or low grade serous carcinomas, important in biopsy for diagnostic and therapeutic orientation due to its high degree of sensitivity to chemotherapy treatment in those with mutation, making this marker one of the most relevant in ovarian tumour pathology.
Keywords: Histología; P53; High-grade serous ovarian carcinoma